2016
DOI: 10.1001/jama.2016.8655
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deutetrabenazine on Chorea Among Patients With Huntington Disease

Abstract: IMPORTANCE Deutetrabenazine is a novel molecule containing deuterium, which attenuates CYP2D6 metabolism and increases active metabolite half-lives and may therefore lead to stable systemic exposure while preserving key pharmacological activity. OBJECTIVE To evaluate efficacy and safety of deutetrabenazine treatment to control chorea associated with Huntington disease. DESIGN, SETTING, AND PARTICIPANTS Ninety ambulatory adults diagnosed with manifest Huntington disease and a baseline total maximal chorea score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 347 publications
(81 citation statements)
references
References 28 publications
4
76
0
1
Order By: Relevance
“…In total, 131 references were retrieved, and 2 studies were included 4, 9. Our evidence network, describing how the included studies related to one another, comprised 1 trial that tested TBZ (TETRA‐HD; n = 84) and another that tested DEU (FIRST‐HD; n = 90), both against placebo (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 131 references were retrieved, and 2 studies were included 4, 9. Our evidence network, describing how the included studies related to one another, comprised 1 trial that tested TBZ (TETRA‐HD; n = 84) and another that tested DEU (FIRST‐HD; n = 90), both against placebo (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike classical neuroleptics, this compound depletes presynaptic dopamine by blocking vesicular monoamine transporter type 2 (VMAT2) 3. Deutetrabenazine (DEU), a structurally related molecule with deuterium (a heavy hydrogen isotype) placed at key positions, was recently tested successfully against placebo 4. Deuteration prolongs half‐life, reduces metabolism variability, and is proposed to translate into less frequent dosing, a lower daily dose, and improved tolerability.…”
mentioning
confidence: 99%
“…the MermaiHD study [47] and the deutetrabenazine trial [48], have detected significant placebo effects. Interestingly, Cubo et al observed a significant placebo effect on behavior, but not on motor symptoms or cognition in a large multicenter drug trial in HD [49].…”
Section: Discussionmentioning
confidence: 99%
“…The added deuterium molecule attenuates CYP2D6 activity, thereby prolonging its half-life. A trial is underway for chorea in Huntington’s disease [154], and it is likely that the indications may expand to tardive dyskinesias and dystonia in the future.…”
Section: Reviewmentioning
confidence: 99%